Multiorgan Dysfunction in Severe Malaria: A Rare Case Report from Bali, Indonesia - Anak Agung Ngurah Satya Pranata; I Made Susila Utama (The Indonesian Journal of Infectious Diseases, 2026)
Background: Severe falciparum malaria remains a major cause of morbidity and mortality in tropical regions and may lead to multiorgan dysfunction, including cerebral malaria, severe anemia, acute kidney injury, and hepatic impairment. Although Bali is considered a non-endemic area, imported malaria cases continue to present significant diagnostic and therapeutic challenges. We report a rare case of severe falciparum malaria with multiorgan involvement in a traveler returning from an endemic region. Case Presentation: A 31-year-old man presented with a two-week history of intermittent high-grade fever accompanied by progressive confusion and incoherent speech one day before admission. He had recently returned from Sumba, an area endemic for malaria. Rapid diagnostic testing for malaria was positive, and peripheral blood smear examination confirmed Plasmodium falciparum trophozoites and gametocytes with a parasite density of 34,855 parasites/μL. Laboratory findings revealed severe malaria complicated by cerebral involvement, anemia, thrombocytopenia, hepatic dysfunction, and acute kidney injury. The patient was treated with intravenous artesunate followed by oral dihydroartemisinin–piperaquine, along with supportive management including intravenous fluids, antipyretics, antiemetics, and blood transfusion. Clinical and laboratory parameters improved progressively, with recovery of consciousness by the third day of treatment. Conclusion: Severe falciparum malaria should be considered in patients presenting with altered mental status and recent travel to malaria-endemic areas, even in non-endemic regions. Early diagnosis, prompt administration of artemisinin-based therapy, and comprehensive supportive care are essential to prevent mortality and improve outcomes in patients with multiorgan dysfunction